An investigation protocol to manage a foodborne outbreak in a disaster event. (20th October 2021) - Mandato, D; Fraulo, P; Romano, A; Mazzone, P; Colarusso, G; Noschese, R; Peruzy, MF; Ambrosio, RL; Galiero, G; Baldi, L
Abstract: Background: During disaster events, the displaced populations living in tent camps are at high risk from foodborne illness outbreaks (FBO) as in these circumstances it is difficult to follow proper hygienic procedures during food handling and storage. When an outbreak occurs, an epidemiological investigation able to identify the source(s) of the exposure is essential to rapidly establish control measures to prevent continuing episodes of illness. This work aimed to evaluate the effectiveness and the applicability under simulated field conditions of an investigation protocol to be used during a FBO. Moreover, the application of the software 'TOSSINFO' for data analysis was evaluated. Methods: In May 2018, a FBO associated with the consumption of a tuna affecting 46 out of 75 people present in a tent camp in southern Italy was simulated. During the simulation, two teams of doctors and veterinarians participated in the investigation. The investigation protocol involved three steps: environmental inspection, epidemiological investigation, and data analysis through TOSSINFO. This software allows calculating different epidemiological indicators, several measures of association, and the visualization of the progression of the outbreak through epidemic curves. Results: At the end of the exercise, both teams were able to trace the source of the infection. After data collection and data analysis, the groups demonstrated a strong association between illness people and tuna consumption. Furthermore, the teams achieved similar Results: RR (7.50 vs 7.01), OR (27 vs 28), and Chi-square (12.1 vs 10.1). Conclusions: The results demonstrated the validity of the procedure and the simple execution of the software analysis. These guidelines represent an opportunity for the implementation of foodborne disease management strategies and could be used throughout the community, leading to an improvement of the Public Health surveillance system. Key messages: These guidelines allow for effective management of a food toxinfection episode. The original software TOSSINFO used in this procedure enables quick and easy identification of infected food.